Structural Concrete : Theory And Design - Hassoun, M. Nadim; Al-Manaseer, A. A. (2015)
"Text on concrete structural design and analysis. Newly updated to reflect the latest ACI 318-14 code, this edition emphasizes a conceptual understanding of the subject, and builds the student's body of knowledge by presenting design methods alongside relevant standards and code"--
Keywords: Reinforced concrete construction; Buildings, Reinforced concrete; TECHNOLOGY & ENGINEERING / Civil / General